POSSIBILITIES AND LIMITS OF TEACHING OF ELECTRICAL ENGINEERING IN BASIC SCHOOLS - SERAFÍN, Čestmír (Trends in education, 2017)
The paper deals with the questions of where and how directed didactic transformation of the electrical field, that this was in line with the objectives of basic education, i.e. that the pupils have created, at a level appropriate to their abilities, skills and learning assumptions, key and professional competencies. The objective of the paper is to give a certain though limited insight into the issue of preparation of students in the electrical engineering area at basic schools. What options inclusion of topics are given and what is for them the limiting factor - in the field of electrical engineering is the concept of the didactic mediation of its educational contents characterized by a wide diversity. This diversity however, it must be in the selection of educational contents supported by the capabilities of the pupil. The didactic mediation of educational content is forcing us to comply with the requirements defined in the curriculum documents, at the same time, however, it is necessary to involve the requirements of other actors and factors affecting the process of education, i.e., practice requirements on the quality of the preparation of the pupil. These two areas, however, unfortunately often in educational practice faces.
Keywords: learning; electrical engineering; elementary school; framework educational programme; technical education